NGX426, an Oral AMPA‐Kainate Antagonist, Is Effective in Human Capsaicin‐Induced Pain and Hyperalgesia - Wallace, Mark S.; Lam, Vicky; Schettler, Jared (Pain medicine (Malden, Mass.), 2012)
Background Non‐N‐methyl‐D‐aspartate receptor subtypes modulate neurotransmitter release and mediate fast excitatory postsynaptic potentials. This study evaluated the effects of an oral prodrug to tezampanel, a selective α‐amino‐3‐hydroxy‐5‐methly‐4‐isoxazole‐proprionic acid/kainate receptor antagonist, on intradermal capsaicin‐induced pain and hyperalgesia. Methods This was a randomized, double blind, crossover, placebo‐controlled study. Eighteen subjects received 150 or 90 mg NGX426, or placebo, separated by a washout of 6 ± 2 days. In each treatment period, two intradermal injections of capsaicin were given in the volar region of alternate forearms at 30‐ and 120‐minute drug/placebo administration. Spontaneous pain, elicited pain, and area of hyperalgesia were determined at certain time points after each injection. Subjects were asked to rate the painfulness of a 1‐minute long 45°C heat stimulus (brief thermal stimulation [BTS]) applied to the anterior thigh at 4 hours and 30 minutes following drug administration, then every 30 minutes through 6 hours following drug administration. Results The 150‐mg dose produced a statistically definitive reduction in spontaneous pain for all time points relative to placebo. The 90‐mg dose produced a statistically significant reduction for the early time point and the entire time interval. Both doses significantly reduced elicited pain at all time points. For the BTS, the 150‐mg group reached statistical significance compared with placebo at the 270‐minute time point only. Conclusions This study demonstrated that NGX426 reduces capsaicin‐induced pain and hyperalgesia in human volunteers with low incidence of side effects that suggests that this class of drug may be effective in the treatment of clinical pain.